THU0025 Effect of Ageing on Anti-Mpo Antibody Mediated Glomerulonephritis in Mice. (9th June 2015) - Wang, Q.; van Timmeren, M.M.; Petersen, A.H.; Yuan, J.; Moorlag, H.; Li, R.; Brouwer, E.B.; Westra, J.; Boots, A.H.; Heeringa, P.
Abstract : Background: Antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) is a typical disease of the elderly. In AAV there is an age-specific increase in disease incidence and age is a predictor of disease outcome 1 . Objectives: In this study we aimed to determine the contribution of age to the development of AAV, employing a mouse model of anti-MPO antibody mediated glomerulonephritis. Methods: Disease was induced in young (3 months) and old (18 months) C57Bl6 mice by injecting mouse anti-MPO IgG i.v. (2.8 mg/mouse) and LPS i.p. (3000 EU/g body weight). Mice were sacrificed at day 1 and 7 (n=7-8/group). Control groups consisted of young and old mice left untreated (n=6/group) or injected with LPS only and sacrificed at day 7 (n=7/group). Plasma IL-6 levels were quantified by ELISA. Neutrophils and monocytes and their activation status were analysed in peripheral blood by flowcytometry. Urine samples were tested for albuminuria by ELISA. Histopathological evaluation of the kidney included quantification of glomerular neutrophil accumulation at day 1 and glomerular crescent formation and glomerular capillary necrosis at day 7. Renal mRNA levels of endothelial cell adhesion molecules (ICAM, VCAM) were analysed by qPCR. Results: Preliminary results indicate that old mice developed more severe disease upon injection of anti-MPO IgG /LPS compared to young mice. This was evidenced at day 1 by increased plasma IL-6 levels (old: median 232.4 pg/ml, range 95.9-6313.3 pg/ml versus young: not detectable) (p<0.05), an increased percentage of circulating activated monocytes (old: 58.7%, range 18.3-75.5% versus young: 30.6%, range 18.5-48.0%) (p<0.05) and increased numbers of glomerular neutrophils (old: 2.0/glomerulus, range 1.5-3.1/glomerulus versus young: 1.1/glomerulus, range 0.2-2.8/glomerulus) (p<0.05) in old mice. Moreover, at day 7, old mice had increased albuminuria (old: 2268 ug/18h, range 126-18700 ug/18h versus young: 569 ug/18h, range 255-1106 ug/18h) (p<0.05) and displayed more glomerular capillary necrosis (old: 11.0%, range 8.0-13.0% versus young: 7.5%, range 3.0-9.0%) (p<0.05). Glomerular crescent formation was mild in young and old mice (old: 5%, range 4-7% versus young: 5%, range 2-8%) and did not differ. At day 7, renal endothelial cell adhesion molecules ICAM mRNA levels (fold induction) (old: 3.0 range: 1.8-5.3 versus young: 1.0 range 0.2-1.8) and VCAM mRNA levels (fold induction) (old: 8.0 range: 1.4-18.6 versus young: 2.6 range 1.2-6.6) were higher in old mice compared to young mice (for both, p<0.05). Conclusions: Our preliminary results suggest that aged mice develop more severe clinical and pathological disease upon induction of anti-MPO IgG/LPS mediated glomerulonephritis. Both age-related changes in the immune system as well as kidney specific changes upon ageing may contribute to this effect. References: Hamour, Sally M., and Alan D. Salama. ANCA comes of age – but with caveats. Kidney international 79.7 (2011): 699-701. Disclosure of Interest: None declared